Pembuatan Aplikasi Pengiriman Berkas - Reyner Wijoyo; Alexander Setiawan; Agustinus Noertjahyana (Jurnal Infra, 2020)
The file sending process still done manually so the sender and recipient don’t know the location of the file and can’t track the file. furthermore, the total cost of sending file outside is still recorded manually so BAUK does not know the costs each unit spent.Because of that problem, file sending application based on website and android was created using PHP, MySql, and Java. Starts by creating a database to save all data and then create a website so that users can view and input data, then proceed with creating an android application using SOA and Rest so website database can be used on android and have the same data.This application can help the process of sending files by recording them automatically, tracking the files location, and see the total cost each unit.